2015
DOI: 10.1016/j.virol.2015.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Membrane association of a nonconserved viral protein confers virus ability to extend its host range

Abstract: Citrus tristeza virus (CTV), the largest and most complex member of the family Closteroviridae, encodes a unique protein, p33, which shows no homology with other known proteins, however, plays an important role in virus pathogenesis. In this study, we examined some of the characteristics of p33. We show that p33 is a membrane-associated protein that is inserted into the membrane via a transmembrane helix formed by hydrophobic amino acid residues at the C-terminal end of the protein. Removal of this transmembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 71 publications
3
31
0
Order By: Relevance
“…2A, white arrows). Similar distribution of the GFP-tagged p33 was observed also under the conditions when p33 was expressed from the native promoter upon virus infection (Kang et al, 2015). Here we extended our microscopy observations to examine the details of the intracellular localization of p33 in order to identify association of the protein with particular cellular structures.…”
Section: P33 Forms Vesicular Structures and Localizes To Pd In Nicotisupporting
confidence: 69%
See 4 more Smart Citations
“…2A, white arrows). Similar distribution of the GFP-tagged p33 was observed also under the conditions when p33 was expressed from the native promoter upon virus infection (Kang et al, 2015). Here we extended our microscopy observations to examine the details of the intracellular localization of p33 in order to identify association of the protein with particular cellular structures.…”
Section: P33 Forms Vesicular Structures and Localizes To Pd In Nicotisupporting
confidence: 69%
“…Agrobacterium tumefaciens-mediated delivery of a cassette encoding the fusion protein into leaves of N. benthamiana plants allowed observation of the distribution of GFP-tagged p33 in cells of the infiltrated leaves. In our recent work, we showed that the GFP:p33 fusion protein accumulated at the cytoplasmic membrane and also formed vesicular bodies distributed throughout the cytoplasm but not in the nucleus (see Kang et al (2015) and Fig. 2A, white arrows).…”
Section: P33 Forms Vesicular Structures and Localizes To Pd In Nicotimentioning
confidence: 82%
See 3 more Smart Citations